- #1

- 43

- 0

Hi,

I've been trying to work out the formula for the sum for the full adder logic, however have come across a gap which I don't know how to fill.

S = (¬A.¬B.C) + (¬A.B.¬C) + (A.¬B.¬C) + (A.B.C)

S = ¬A.(¬B.C + B.¬C) + A.(¬B.¬C)

S = ¬A.(B [tex]\oplus[/tex] C) + A.( do not know what to do at this point to reach the next stage

S = (A [tex]\oplus[/tex] B) [tex]\oplus[/tex] C

Does anyone know how to get to that last statement?

Thanks for any help.

I've been trying to work out the formula for the sum for the full adder logic, however have come across a gap which I don't know how to fill.

S = (¬A.¬B.C) + (¬A.B.¬C) + (A.¬B.¬C) + (A.B.C)

S = ¬A.(¬B.C + B.¬C) + A.(¬B.¬C)

S = ¬A.(B [tex]\oplus[/tex] C) + A.( do not know what to do at this point to reach the next stage

S = (A [tex]\oplus[/tex] B) [tex]\oplus[/tex] C

Does anyone know how to get to that last statement?

Thanks for any help.

Last edited: